Physical activity patterns in adults who are blind as assessed by accelerometry. - Marmeleira, José (2015)
The main purpose of our study was to quantify, by using accelerometry, daily physical activity (PA) in adults with visual impairments. Sixty-three adults (34.9% women) who are blind (18-65 years) wore an accelerometer for at least 3 days (minimum of 10 hr per day), including 1 weekend day. Nineteen participants (~30%) reached the recommendation of 30 min per day of PA, when counting every minute of moderate or greater intensity. No one achieved that goal when considering bouts of at least 10 min. No differences were found between genders in PA measures. Chronological age, age of blindness onset, and body mass index were not associated with PA. We conclude that adults who are blind have low levels of PA and are considerably less active compared with the general population. Health promotion strategies should be implemented to increase daily PA for people with visual impairments.